INDACO project: a pilot study on incidence of comorbidities in COPD patients referred to pneumology units - Fumagalli, Giorgio; Fabiani, Fabrizio; Forte, Silvia; Napolitano, Massimiliano; Marinelli, Paolo; Palange, Paolo; Pentassuglia, Antonella; Carlone, Stefano; Sanguinetti, Claudio Maria (Multidisciplinary Respiratory Medicine, 2013)
Background: Chronic Obstructive Pulmonary Disease (COPD) is often associated with comorbidities, especially cardiovascular, that have a heavy burden in terms of hospitalization and mortality. Since no conclusive data exist on the prevalence and type of comorbidities in COPD patients in Italy, we planned the INDACO observational pilot study to evaluate the impact of comorbidities in patients referred to the outpatient wards of four major hospitals in Rome. Methods: For each patient we recorded anthropometric and anamnestic data, smoking habits, respiratory function, GOLD (Global initiative for chronic Obstructive Lung Disease) severity stage, Body Mass Index (BMI), number of acute COPD exacerbations in previous years, presence and type of comorbidities, and the Charlson Comorbidity Index (CCI). Results: Here we report and discuss the results of the first 169 patients (124 males, mean age 74±8 years). The prevalence of patients with comorbidities was 94.1% (25.2% of cases presented only one comorbidity, 28.3% two, 46.5% three or more). There was a high prevalence of arterial hypertension (52.1%), metabolic syndrome (20.7%), cancers (13.6%) and diabetes (11.2%) in the whole study group, and of anxiety-depression syndrome in females (13%). Exacerbation frequency was positively correlated with dyspnea score and negatively with BMI. Use of combination of bronchodilators and inhaled corticosteroids was more frequent in younger patients with more severe airways obstruction and lower CCI. Conclusions: These preliminary results show a high prevalence of comorbidities in COPD patients attending four great hospitals in Rome, but they need to be confirmed by further investigations in a larger patients cohort.